Fertility Evaluation of Coral Reef Ecosystems Using Bioindicators of Phytoplankton in Watu Lawang Waters, Pasir Putih Beach, Situbondo - Indonesia - Ma'arif, Muhammad Chusnan; Munir, Misbakhul; Akhwady, Rudhy (Journal of Marine Resources and Coastal Management, 2020)
The level of waters fertility is closely relate to the abundance and composition of plankton. Phytoplankton is a biological parameter that can be used as an indicator of the fertility of a waters. The purpose of this study was to determined the community structure of phytoplankton and the level of fertility in the waters of Pasir Putih beach, Situbondo. The study was conducted at five stasions in Watu Lawang waters, Pasir Putih Beach, Situbondo. The Sampling used purposive sampling method. Seawater samples were filtered on the surface of each station using plankton net number 25. Then, water samples were identified in the Microbiology Laboratory of UIN Sunan Ampel Surabaya. The results of identification of phytoplankton in the waters of Watu Lawang, Pasir Putih Beach, Situbondo obtained 4 classes that consisted of Bacillariophyceae, Cyanophyceae, Chlorophyceae, and Dinophyceae family. The phytoplankton composition found during the study was dominated by the Bacillariophyceae class. The genus Bacteriastrum sp and Chaetoceros sp were found in all observation stations. The highest phytoplankton abundance was at station IV with an abundance of 1670 cells L-1. And the lowest abundance of phytoplankton was at station I with an abundance value of 730 cells L-1. The diversity of phytoplankton was categorized in the low diversity level (H’<2.3). The Uniformity index value was classified as unstable (0 <E <0.5). On the other hand, The average value of the Saprobic Index in the waters of Watu Lawang, Pasir Putih, Situbondo was 1.6 which was classified as the Oligosaprobic phase (very slight polluted).